KESEHATAN DAN KESELAMATAN KERJA, INSENTIF FINANSIAL TERHADAP SEMANGAT KERJA KARYAWAN DI PT. HARIND SARANA GRAHA UTAMA KUTA BADUNG - sri maitri (Jurnal Ilmiah Manajemen & Bisnis, 2016)
Human resources is the most important resource that must be owned by an organization. Industry increasingly fierce competition requires companies to optimize available resources so as to survive in the competition. Human resources as labor can not be separated from issues related to health. Occupational health and safety programs is a very important program that should be implemented to employees in particular parts of the field. In addition to occupational health and safety program companies must also consider incentives to support employee spirit. It is interesting to study in order to know how the relationship between the implementation of health, safety and financial incentives of employee spirit. Based on the subject matter, the purpose of this study was to determine the relationship of the implementation of health, safety to employee spirit.The data analysis techniques used in this study was qualitative interpretative data analysis techniques, the analysis of data obtained by researchers reasoning ability in connecting facts and data information. The results of this research was the implementation of health and safety such as the provision of facilities such as BPJS very instrumental in improving employee morale and incentive programs conducted every year was instrumental to boost morale but should be given every month. Based on the results of the analysis, it is suggested that future researchers conduct similar research on other organizations to strengthen and enrich the theories that have been there.